Faktor-Faktor yang Mempengaruhi Pemerintah DKI Jakarta Dalam Mengatasi Penyalahgunaan Fungsi Trotoar di Tanah Abang - Achmad Fachri Fadlullah Salis; Sulistyowati -; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Abstract. In Jakarta, the sidewalks still have various problems to be solved, such as the number of street vendors who open stalls on the sidewalks causing pedestrian space, sidewalks, sidewalks used for illegal parking facilities covering sidewalks, narrow sidewalks, to sidewalks used bikers to break through congestion. Density of existing activities in Tanah Abang cause it does not escape the various forms of misuse of sidewalk function. Therefore, the Government of DKI Jakarta has an obligation to restore the function of the sidewalk by sticking to UU no. 22 Tahun 2009 about Traffic and Road Transportation, Perda no. 5 Tahun 2014 about Transportation, and Perda no. 8 Tahun 2007 about Public Order which in these three regulations contains the functions of the sidewalks and prohibitions to misuse its functions This research aims to determine what factors affect the Government of DKI Jakarta in overcoming misuse of sidewalk function in Tanah Abang and the obstacles that exist at the time of policy implementation. The method used in this study is qualitative, by doing data collection techniques using interviews, observation, and documentation. Data analysis performed with data reduction phase, data presentation, conclusion and verification. The research object is the staff of Transportation Department of DKI Jakarta Province, Central Jakarta Satpol PP, and Tanah Abang Sub-district. The result of the research shows that there are several factors influencing the Government of DKI Jakarta to overcome the misuse of sidewalk function in Tanah Abang namely social condition, organizational relationship, resources, and implementor institution. The obstacles that exist in the implementation of the policy are divided into two internal and external. Internal barriers include low social conditions and low public awareness. External barriers include weak regulation, inadequate market facilities, insufficient human resources, and limited budgets. Keyword: Policy Implementation, Sidewalk, Tanah Abang